Increased neutrophil extracellular trap formation in oligoarticular, polyarticular juvenile idiopathic arthritis and enthesitis-related arthritis: biomarkers for diagnosis and disease activity - Tang, Hongxia; Zhong, Yucheng; Wu, Yali; Huang, Yanmei; Liu, Yi; Chen, Jing; Xi, Ting; Wen, Yini; He, Ting; Yang, Shanshan; Liu, Fan; Xiong, Runji; et al. (Frontiers in Immunology, 2024)
Objective. Neutrophil extracellular traps (NETs) are important factors in initiating and perpetuating inflammation. However, the role of NETs in different subtypes of juvenile idiopathic arthritis (JIA) has been rarely studied. Therefore, we aimed to explore the ability of JIA-derived neutrophils to release NETs and the effect of TNF-α (tumor necrosis factor-alpha) inhibitors on NET formation both in vitro and in vivo, and evaluate the associations of NET-derived products with clinical and immunerelated parameters.Methods. The ability of neutrophils to release NETs and the effect of adalimumab on NET formation was assessed via in vitro stimulation and inhibition studies. Plasma NET-derived products were detected to assess the incidence of NET formation in vivo.Furthermore, flow cytometry and western blotting were used to detect NET-associated signaling components in neutrophils.Results. Compared to those derived from HCs, neutrophils derived from patients with oligoarticular-JIA, polyarticular-JIA and enthesitis-related arthritis were more prone to generate NETs spontaneously and in response to TNF-α or PMA in vitro.Excessive NET formation existed in peripheral circulation of JIA patients, and elevated plasma levels of NET-derived products (cell-free DNA and MPO-DNA complexes) could accurately distinguish JIA patients from HCs and were positively correlated with